2012
DOI: 10.1590/s0102-695x2012005000118
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological screening and acute toxicity of bark roots of Guettarda platypoda

Abstract: Due to its folk use, scientifi c reports and phytochemical screening, the purpose of this work was to study the phytochemical and the biological properties of the methanol extract and to evaluate the anti-infl ammatory activity as well as determine the acute toxicity, antitumor and cytotoxic activity of the root barks of Guettarda platypoda DC., Rubiaceae. In this analysis the presence of fl avonoids and therpenoids were identifi ed. These data and the ones in the literature indicated it as a potential antioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Treatment with HFNE was performed at a single high dose corresponding to 3 g/kg of extract per animal. Since no death or toxic signals were observed, LD50 could not be estimated and HFNE, suggesting that HFNE may be considered non-toxic [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment with HFNE was performed at a single high dose corresponding to 3 g/kg of extract per animal. Since no death or toxic signals were observed, LD50 could not be estimated and HFNE, suggesting that HFNE may be considered non-toxic [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Acute toxicity studies were performed using both sexes of mice according to Pina et al (2012) [ 30 ], with some modifications. Treated groups received a single dose of HFNE (5% of MOD®, 5% of surfactants (HLB of 10.75), 5% of hexane-soluble fraction from fruits of M. subsericea and 85% of water) by oral route, corresponding to 3 g/kg of extract.…”
Section: Methodsmentioning
confidence: 99%
“…In this experiment, these compounds were defined as indole alkaloids ( 1 , 5 ), iridoids ( 2 , 3 ), steroid ( 4 ), triterpenoids ( 7 , 9 ), and polyhydroxy cyclic acids ( 6 , 8 ). Pharmacological studies on G. platypoda have reported the synergistic action of quinic acid glycosides with β-sitosterol and triterpenes with anti-inflammatory activity, while the mechanism of β-sitosterol is comparable to hydrocortisone [32]. Most of the Rubiaceae species also contained iridoids and indole alkaloids [40], which are known to possess anti-inflammatory activities [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Cucumis sativus L (generic name cucumber), from the family Cucurbitaceae, is an important restorative plant with different pharmacological benefits, generally utilized in traditional drug therapies such as Unani, Ayurveda, Siddha, Traditional Chinese. Previous studies done on the plant demonstrated that the plant has numerous essential phytoconstituents like glycosides, flavones, terpinoids, phytosterol, saponins and anolignan B, tannins, ellargic corrosive, glucose, fructose [ 10 ]. These mixes were observed to be involved in a number of the pharmacological exercises, for example, antibacterial, antifungal, antidiabetic, cytotoxic, antacid and carminative movement, hepatoprotective action, and wound healing activities.…”
Section: Introductionmentioning
confidence: 99%